A pathological complete response after combined chemotherapy of gemcitabine and cisplatin in laterally advanced extrahepatic cholangiocarcinoma: a case report - Yamazoe, Sadaaki (Tando, 2022)
The patient was a 71-year-old male with a chief complaint of itching and jaundice. Detailed physical examinations revealed that his condition was diagnosed as laterally advanced extrahepatic cholangiocarcinoma. To obtain the R0 resection, right or left trisectionectomy with pancreatoduodenectomy was needed. We informed him of the treatment strategy such as resection, chemotherapy and second opinion, he selected chemotherapy. Chemotherapy using gemcitabine and cisplatin was initiated and computed tomography after 4 cycles revealed that the tumor had decreased. After 13 cycles, right hepatectomy with caudate lobectomy and extrahepatic bile duct resection was performed as conversion surgery. As a result, a pathological complete response was achieved in the primary tumor. Although he did not receive any further adjuvant chemotherapy, no recurrent lesions have been detected for 28 months after the surgery.